The Neurological Traces of Look-Alike Avatars - Gonzalez-Franco, Mar; Bellido, Anna I.; Blom, Kristopher J.; Slater, Mel; Rodriguez-Fornells, Antoni (Frontiers in Human Neuroscience, 2016)
We designed an observational study where participants (n=17) were exposed to pictures and look-alike avatars pictures of themselves, a familiar friend or an unfamiliar person. By measuring participants’ brain activity with Electroencephalography (EEG), we found face-recognition Event Related Potentials (ERPs) in the visual cortex, around 200-250 ms, to be prominent for the different familiarity levels. A less positive component was found for self-recognized pictures (P200) than pictures of others, showing similar effects in both real faces and look-alike avatars. A rapid adaptation in the same component was found when comparing the neural processing of avatar faces vs. real faces, as if avatars in general were assimilated as real face representations over time. ERP results also showed that in the case of the self-avatar the P200 component correlated with more complex conscious encodings of self-representation, i.e. the difference in voltage in the P200 between the self-avatar and the self-picture was reduced in participants that felt the avatar looked like them. This study is put into context within the literature of self-recognition and face recognition in the visual cortex. Additionally, the implications of these results on look-alike avatars are discussed both for future Virtual Reality and neuroscience studies.